An Investigation of the Attitudes of Teachers on the Use of Newspapers in the Teaching of Turkish as a Foreign Language According to Some Variables * - Ertan Miyanyedi; Bünyamin Celik (International Journal of Social Sciences & Educational Studies, 2020)
In recent years, many studies have been conducted on teaching Turkish as a foreign language. While some of these researches involve teaching language skills, some involve developing materials. As well as the materials developed in this field, the beliefs of the language teachers who will apply these materials will affect the use of these developed materials and their benefits to students. One of the materials that can be used in teaching Turkish as a foreign language is newspapers, also considered as authentic materials. In the researches, it has been stated that the classrooms where newspapers are used have positive effects on students’ interest and participation in the lesson. As the starting point of this research, it was tried to determine which opinions and attitudes the teachers who teach Turkish to foreigners have towards using newspaper in their lessons. The research was conducted with a descriptive method-based screening model. For this purpose, teachers who teach Turkish abroad were contacted via internet and a questionnaire was conducted with them. In the analysis of the data obtained from the questionnaire, the frequency and percentages of the items were calculated. As a result, it was determined that there was no significant difference of opinion between teachers’ views on gender, age, graduated school and experience, and teachers were in agreement that students would participate more actively in the course in the development of vocabulary, development of reading comprehension skills when newspapers are used in lessons. It is thought that this research will be a source for material development studies for the use of newspapers in lessons.